Endocrine therapy with accelerated Partial breast irradiatiOn or exclusive ultra-accelerated Partial breast irradiation for women aged ≥ 60 years with Early-stage breast cancer (EPOPE): The rationale for a GEC-ESTRO randomized phase III-controlled trial. (July 2021) - Hannoun-Levi, Jean-Michel; Chamorey, Emmanuel; Boulahssass, Rabia; Polgar, Csaba; Strnad, Vratislav; ,
Highlights: Epidemiologic data confirm the increase of breast cancer incidence in the elderly. The risk of recurrence of breast cancer is basically low. De-escalation breast cancer adjuvant therapy is justified in selected elderly patients. Ultra-accelerated breast irradiation with endocrine therapy omission is under debate. Prospective randomized trial is warranted. Abstract: Purpose: Breast cancer in the elderly has become a public health concern; there is a need to re-design its treatment with a view to de-escalation. Our paper sets out the rationale for a phase 3 randomized trial to evaluate less burdensome adjuvant procedures that remain effective and efficient. Materials and methods: For low-risk breast cancer in the elderly, adjuvant treatment has been adjusted in order to make it more suitable and efficient. Hypofractionated radiation therapy based on accelerated or non-accelerated regimens as well as accelerated and ultra-accelerated partial breast irradiation (APBI) protocols were reviewed. Withdrawal of radiation (RT) or endocrine therapies (ET) from the adjuvant procedure were also investigated. Based on molecular and APBI classifications, inclusion criteria were discussed. Results: Phase 3 randomized trials which compared standard vs. accelerated/non-accelerated hypofractionated regimens confirmed that the latter were non-inferior in terms of local control. Similarly, except for intraoperative-based techniques, APBI achieved non-inferior local control rates compared to whole breast irradiation for low-risk breast cancer. In phase 2 prospective trials using ultra APBI, encouraging results were observed regarding oncological outcome and toxicity profile. In phase 3 trials, adjuvant ET without RT significantly increased the rate of local relapse with no impact on overall survival while RT alone proved effective. Elderly patients aged 60 or more with low-risk, luminal A breast cancer were chosen as the target population in a phase 3 randomized trial comparing APBI + 5-year ET vs. uAPBI (16 Gy 1f) alone. Conclusion: To investigate de-escalation adjuvant treatment for elderly breast cancer patients, we have defined a road map for testing more convenient strategies. This EPOPE phase 3 randomized trial is supported by the GEC-ESTRO breast cancer working group.